2009
DOI: 10.1111/j.1755-0998.2009.02516.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of DNA isolation from historical otoliths on nuclear–mitochondrial marker amplification and age determination in an overexploited fish, the common sole (Solea solea L.)

Abstract: Historical otolith collections are crucial in assessing the evolutionary consequences of natural and anthropogenic changes on the demography and connectivity of commercially important fish species. Hence, it is important to define optimal protocols for purifying DNA from such valuable information sources while avoiding any damage to the physical structure of the otolith. Before being able to conclude on the harmlessness of a method, it is important to validate protocols on different kinds of otoliths by testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Indeed, otoliths represent a limited source of DNA since only two otoliths per fish can be collected; otolith collections are very valuable. According to Cuveliers et al (2009), a trade-off must be found between DNA quality and otolith preservation. Contrasting conclusions were given for several species concerning the effect of DNA extraction on ageing success (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, otoliths represent a limited source of DNA since only two otoliths per fish can be collected; otolith collections are very valuable. According to Cuveliers et al (2009), a trade-off must be found between DNA quality and otolith preservation. Contrasting conclusions were given for several species concerning the effect of DNA extraction on ageing success (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Contrasting conclusions were given for several species concerning the effect of DNA extraction on ageing success (e.g. Cuveliers et al 2009). It underlines the importance of minimizing the damage to the otolith, depending on the method used and different factors such as incubating time or concentration of EDTA or SDS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies have shown that a number of different extraction methods can provide consistent yields of DNA with sufficient quality for amplification of various genetic markers (see Cuveliers et al . and Therkildsen et al . ).…”
Section: Introductionmentioning
confidence: 91%
“…Based on previous studies, it is known that the DNA on fish scales and otoliths is only available in low quantities and that it can be highly degraded (Hutchinson et al 1999;Nielsen et al 1999). However, recent studies have shown that a number of different extraction methods can provide consistent yields of DNA with sufficient quality for amplification of various genetic markers (see Cuveliers et al 2009 andTherkildsen et al 2010). Furthermore, it has been demonstrated that the DNA from historical otoliths can also be used for medium-and high-throughput SNP genotyping (Poulsen et al 2011;Therkildsen et al 2013).…”
Section: Introductionmentioning
confidence: 99%